Role of Electrostatic Effects in the Pure Component and Binary Adsorption of Ethylene and Ethane in Cu-Tricarboxylate Metal-Organic Frameworks - Timothy M. Nicholson; Suresh K. Bhatia (Adsorption Science & Technology)
The interaction of ethane and ethylene with a Cu-tricarboxylate complex was investigated, showing that at low loadings the lighter molecule has a higher binding energy as a result of interaction with framework Cu and H-bonding with basic framework oxygen atoms. This leads to the selective adsorption of ethylene at low pressure by a factor of ca. 2. This is overcome by the stronger van der Waals interaction of ethane at high loadings, explaining recent literature data. Both experimental data and single-component Grand Canonical Monte Carlo (GCMC) simulations were fitted well with the Unilan model and mixture isotherms were satisfactorily predicted by the Ideal Adsorbed Solution Theory when compared with binary simulation results. Both binary GCMC simulations and Ideal Adsorbed Solution Theory predictions yielded separation factors of ca. 2 and a difference in isosteric heat of 3 kJ/mol. The results suggest that the Cu-BTC framework offers a possible route for the separation of ethane and ethylene, a Holy Grail of adsorption.